Pengaruh Ekstrak Daun Asian Ticktrefoil (Desmodium heterocarpon (L.) DC.) dan Bonggol Nanas (Ananas comosus (L.) Merr.) sebagai Pestisida Nabati terhadap Intensitas Serangan Serangga Hama pada Tanaman Sawi Hijau (Brassica juncea L.) - Ainiyyah Nur Azizah; Sonja Verra Tinneke Lumowa; Dora Dayu Rahma Turista; Akhmad Akhmad (Biocaster : Jurnal Kajian Biologi, 2026)
The study aimed to determine the effect of Asian Ticktrefoil leaf extract (Desmodium heterocarpon (L.) DC.) and Pineapple Weevil (Ananas comosus (L.) Merr.) as botanical pesticides on the intensity of insect pest attacks on Green Mustard (Brassica juncea L.) plants. This type of research is an experimental study conducted in the Agricultural Land of Jalan Jayakarta RT. 19, Rawa Makmur Village, Palaran District, Samarinda City. The research design used a Randomized Block Design (RBD) with 5 treatments, namely: T0 (control), T1 (detergent + water), T2 (50% Asian ticktrefoil leaf extract), T3 (50% pineapple weevil extract), and T4 (50% combination of Asian ticktrefoil leaf and pineapple weevil extract) with 5 replications. The data analysis results showed that the calculated F for each treatment, respectively, was (457.05) > F (4.77) at a significance level of 1%. This demonstrates a highly significant effect of the application of Asian Ticktrefoil (Desmodium heterocarpon (L.) DC.) leaf extract and Pineapple Weevil (Ananas comosus (L.) Merr.) as botanical pesticides on the intensity of insect pest attacks on mustard greens (Brassica juncea L.). These findings demonstrate the potential of locally sourced botanical pesticides as an environmentally friendly pest control alternative in mustard greens cultivation.